Profitability, Leverage, Company Size, Environmental Performance and Corporate Social Responsibility Disclosure in Indonesia: The Moderating Effect of Company Profile - Citra Amaliyah; Winda Tri Wahyuni; Nisa Agustina; Rawi Rawi (Cita Konsultindo Research Center, 2024)
This study aims to examine the effect of profitability, leverage, company size, environmental performance in financial and non-financial reports on corporate social responsibility disclosure (CSRD), with company profile as a moderating variable. This type of research is included in quantitative associative research. The sampling method uses purposive sampling, with a sample size of 85 companies. Data was taken from 521 companies on the Indonesia Stock Exchange covering various sectors in the 2018-2022 period. The data analysis method used in this research is descriptive statistical analysis, classical assumption test and moderated regression analysis (MRA) using IBM SPSS 29. The results showed that profitability, company size, environmental performance have a positive effect on CSR disclosure. Company profile moderates company size and environmental performance on CSR disclosure while leverage has no negative effect on CSR disclosure. Company profile does not moderate profitability and leverage on CSR disclosure.